Three Approaches to Writing School Programs with Official Language Minorities : Research Brief no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Trois approches pour rédiger des programmes scolaires avec les minorités de langue officielle : Résumé de recherche no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Resolution 2021-04 : Request to Revise and Improve the Secondary III and Secondary IV History of Quebec and Canada Curriculum - Quebec Federation of Home and School Associations (QFHSA) (2021)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)
Number of pages: 24

Resolution 2017-04 : Quebec Secondary III and IV History Curriculum: In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

Quebec's Secondary III & IV History Curriculum : In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2016)